2010
DOI: 10.1186/1472-6920-10-74
|View full text |Cite
|
Sign up to set email alerts
|

Supervision and feedback for junior medical staff in Australian emergency departments: findings from the emergency medicine capacity assessment study

Abstract: BackgroundClinical supervision and feedback are important for the development of competency in junior doctors. This study aimed to determine the adequacy of supervision of junior medical staff in Australian emergency departments (EDs) and perceived feedback provided.MethodsSemi-structured telephone surveys sought quantitative and qualitative data from ED Directors, Directors of Emergency Medicine Training, registrars and interns in 37 representative Australian hospitals; quantitative data were analysed with SP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 12 publications
2
31
0
1
Order By: Relevance
“…This study alone showed that access block, independent of overcrowding, affects patients. Jelinek et al 13 also showed that overcrowding in the ED affects the supervision of junior doctors.…”
Section: 急症室病人滯留和過度擁擠的管理策略和 解決方案mentioning
confidence: 99%
“…This study alone showed that access block, independent of overcrowding, affects patients. Jelinek et al 13 also showed that overcrowding in the ED affects the supervision of junior doctors.…”
Section: 急症室病人滯留和過度擁擠的管理策略和 解決方案mentioning
confidence: 99%
“…ED doctors, particularly those who were more senior, also had no reluctance in allowing junior medical staff to manage patients with advanced cancer under appropriate supervision, as is usual in most other acute emergency presentations 13. ED nurses in contrast were much more likely to feel this ‘usual practice’ was inappropriate for patients with advanced cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Supervisi model Proctor yang dilaksanakan secara efektif melalui kegiatan bimbingan, umpan balik dilakukan pada masalah yang dihadapi untuk pengembangan personal, peningkatan pengetahuan, pemberian dukungan akan meningkatkan profesionalisme, meningkatkan kesadaran diri perawat sehingga dapat memengaruhi keselamatan pasien (Jelinek, et al, 2010). Hasil penelitian ini diperkuat oleh hasil penelitian Rumampuk yang menyatakan bahwa semakin baik supervisi yang dilakukan kepala ruang akan meningkatkan pelaksanaan keselamatan pasien oleh perawat pelaksana (Rumampuk, 2013).…”
Section: Hasilunclassified